Islamic Service Development: Analysis Of Customer Satisfaction In The Cafeteria Of Muhammadiyah Mataram University - Agustina, Ahadiah; Syahrani, Risma; Saputra, Dalingga (Universitas Muhammadiyah Mataram, 2021)
Fostering Islamic services for the college canteen is very important to maintain business continuity. At Muhammdiyah University Mataram, canteen consumers include students, employees, and lecturers. Based on the level of implementation of management, operations, completeness of facilities and infrastructure, as well as services, the canteen of Muhammadiyah Mataram University becomes canteen A, B+, and B. This research aims to foster Islamic canteen services at Muhammadiyah Mataram University. This development is carried out by qualitative methods related to aspects of halal food, food safety, halal food, location comfort, and price involving 10 respondents. The results showed still lack of customer satisfaction with canteen service at Muhammdiyah Mataram University. the most dominant variable that affects the performance of canteens A and B is food halalness. Managers of canteen A and canteen B can make alternatives to Islamic service standards and halal menu production and uniform prices in order to create healthy business competition. Canteen at Muhammdiyah University Mataram is expected to have a special sales area to minimize biological or physical contamination. The manager of the canteen of Muhammdiyah Mataram University is expected to pay more attention to the condition of the canteen to create a more comfortable atmosphere as a place to eat and discuss, as a description of the college canteen. Halal certification is expected.